PENGARUH PENDAPATAN, GAYA HIDUP DAN LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA PROGRAM STUDI MANAJEMEN UNIVERSITAS YPPI REMBANG - Fahrudin Fahrudin; Wulan Suryandani (Politeknik Negeri Ambon, 2026)
Introduction: Students are often driven by specific motivations to acquire the products they need to fulfill their needs. This is because they tend to be tempted by popular or branded items. Moreover, many companies are focusing on students or the younger generation as their target market. Technological advancements are making it easier for students to stay informed about new trends and access these products, thus making them spend their money more quickly, not just on everyday items.Methods: This study used a quantitative method. The research object was YPPI Rembang University students with a population of 201 students and a sample of 67 respondents determined using proportional sampling techniques. The research instrument was a questionnaire. The data analysis technique used was multiple linear regression, while the data processing was carried out using the SPSS application.Results: The results of the study indicate that income has a negative and significant effect on financial behavior, meaning that higher respondents' income does not always lead to better financial behavior; it can even trigger less wise financial behavior. Furthermore, this study also found that lifestyle has a positive and significant effect on financial behavior, so that the better the lifestyle management, the better the financial behavior of students. In addition, financial literacy has been shown to have a positive and significant effect on financial behavior, indicating that the higher the level of financial literacy possessed by students, the better their ability to manage their finances responsibly. Keywords: Financial Behavior, Financial Literacy, Income, Lifestyle, Students.